2000
DOI: 10.1207/s15326942dn1802_2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Lead Levels and Language Processing Performance

Abstract: The relation between bone lead absorption and language processing abilities in 156 randomly selected 11- to 14-year-old boys who were asymptomatic for lead toxicity is examined. Tibial lead concentrations were measured by X-ray fluorescence spectroscopy. The language processing outcome variables consisted of the least and most difficult subtests from the Nonword Repetition Task, Competing Language Processing Task, and the Revised Token Test. Participants were classified by quartiles according to bone lead conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…Despite knowing that the human being uses (expressive lexicon) a lower number of words than he is able to understand (receptive lexicon), this is not always verified by evaluation instruments. The reason for this is that the language evaluation through tests has a certain degree of artificiality, that is, many times the way we check a word comprehension depends on the As described in the introduction, several studies have found developmental disorders in children, including language disorders, caused by the lead exposure specially in cases where the blood metal concentration is above the tolerable value, of 10 g/dl (1,5,6). Despite not finding a significant correlation between the contamination level and the language development, this study points out that the contamination by lead can constitute a risk factor for language development disorders for the studied children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite knowing that the human being uses (expressive lexicon) a lower number of words than he is able to understand (receptive lexicon), this is not always verified by evaluation instruments. The reason for this is that the language evaluation through tests has a certain degree of artificiality, that is, many times the way we check a word comprehension depends on the As described in the introduction, several studies have found developmental disorders in children, including language disorders, caused by the lead exposure specially in cases where the blood metal concentration is above the tolerable value, of 10 g/dl (1,5,6). Despite not finding a significant correlation between the contamination level and the language development, this study points out that the contamination by lead can constitute a risk factor for language development disorders for the studied children.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies reveal that elevated lead levels are able to influence the development of distinct cognitive skills, having some finding, also, association between lead concentration and the performance in the evaluated cognitive abilities, the results still are incongruous (4)(5)(6). Some authors suggest that even lower lead levels than the accepted by the World Health Organization present risk for disorders in the skills mentioned above, indicating that a security margin does not exist for lead exposure (3,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…that increasing bone lead levels (10-53 ppm) was significantly associated with poorer performance on complex language processing tasks (e.g., 4-syllable Nonword Repetition Task, subset 8 of Revised Token Task, responding to spoken commands) (Campbell et al 2000b). Covariates considered in the analysis included child age, race, SES, and maternal IQ.…”
Section: Health Effectsmentioning
confidence: 99%
“…At these levels, over a quarter of American children are exposed to lead levels sufficient to cause neurological dysfunction (Bernard and McGeehin 2003). In children, lead is linked to an impaired ability to form verbal concepts (Baker et al 1983), reason grammatically (Needleman et al 1990), and follow commands (Campbell et al 2000). Reading comprehension, reading ability, and vocabulary performance are thus all adversely affected by lead exposure (Lanphear et al 2000;Surkan et al 2007).…”
Section: Effect Of Lead On the Central Nervous Systemmentioning
confidence: 99%